Switch Pocket Kinase: An Emerging Therapeutic Target for the Design of Anticancer Agents - Kaur, Charanjit; Sharma, Bhargavi; Nepali, Kunal (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Protein kinases are amongst the most focused enzymes in the current century to design, synthesize and formulate drugs that ought to be effective in the treatment of various disordered and diseased states involving either overexpression or deficiency situations. The ATP pocket on the kinases is the active binding site for most of the kinase inhibitors. However, the kinase mutations prevent the binding of kinase inhibitors to the ATP pocket. The enzyme becomes inactive even in the mutated state when the switch pocket site on the enzyme is occupied by switch pocket inhibitors. This review comprises detailed information regarding various classical protein kinases and switch pocket kinase inhibitors with their mechanism of action so that new molecules can be designed to encounter mutations in the kinase enzyme.
Keywords: protein kinases